Exploring the Pathophysiology of Adenomy osis in Jakarta: Novel Insights into I nflammatory Pathways and Angiogenesis - Suryani, Febria; Rodriguez, Maria (Phlox Institute: Indonesian Medical Research Organization, 2023)
Introduction: Adenomyosis, characterized by endometrial glands and stroma within the my ometrium, is a significant cause of morbidity (abnormal uterine bleeding (AUB), pain, infertility) among women globally. While its general pathophysiol ogy is increasingly understood, population-specific data, particularly f rom diverse Asian populations like that of Jakarta, Indonesia, remains limited. This study aimed to investigate the roles of specific inflammatory pathways and angiogenic factors in adenomyosis within a cohort of women in Jakarta, hypothesizing that common pathogenic mechanisms manifest in this population, potentially influenced by local factors. Methods: This prospective c ase-control study was conducted in three tertiary referral hospitals in Jakarta, Indonesia from January 2022 to December 2024. Fifty women undergoing hysterectomy, diagnosed with adenomyosis were recruited, alongside 50 cont rol women without adenomyosis undergoing hysterectomy for other benign conditions. Samples of eutopic endometrium, ectopic adenomyotic lesions, and associated myometrium were collected. Immunohistochemistry quantified inflamm atory cells (macrophages, mast cells, T-lymphocytes) and microvessel density (CD31). Expression of key inflammatory cytokines and angiogenic factors was assessed via qRT-PCR and ELISA. Results: Women with adenomyosis in th e Jakarta cohort exhibited significantly increased infiltration of M1-phenotype macrophages (p0.001) and mast cells (p0.001) in adenomyotic lesions and eutopic endometrium compared to controls. IL-6, TNF-α, and MCP-1 expression was markedly upregulated in adenomyotic foci (all p0.001). Microvessel density, VEGF-A, and VEGFR2 expression were significantly elevated in adenomyotic tissue (all p0.001). Strong positive correlations were observed between macrophage density, IL-6 levels, VEGF-A expression, and microvessel density within adenomyotic lesions, similar to findings in other populations. Conclusions: This study, conducted in Jakarta, provides strong evidence for a heightened pro-inflammatory and pro-angiogenic microenvironment in adenomyosis, consistent with general pathogenic theories. These findings i n an Indonesian population underscore the universal importance of th ese pathways and suggest that novel therapies targeting inflammation and angiogenesis could be relevant for women in this region. Further research should explore potential local modulatory factors.